ANALISIS SEMIOTIKA MOTIF UKIRAN PADA LANGGAR UKIR DI DESA MARGOMULYO TAYU-PATI - Fatimah, Nurul (FIHROS: Jurnal Sejarah dan Budaya, 2024)
Abstract This research aims to; Identifying various carving motifs found in Langgar Ukir in Margomulyo Tayu-Pati Village and analyzing and interpreting the meaning of carving motifs in Langgar Ukir in Margomulyo Tayu-Pati Village. The approach used in this study is a qualitative approach. Apart from using historical research stages, researchers also use the Content Analysis method, which is a method used to examine symbolic phenomena in order to reveal phenomena which constitute the content, meaning and essential elements in works of art. This research will borrow thoughts from Charles Sanders Peirce regarding Triadic semiotic theory which is used as an analytical tool to answer research problems. The results of this research show that there are various forms of carvings consisting of shapes that resemble animals and plants. Keywords: Semiotics, Carving Breaks, Carving Motifs